Shifty's boys [large type] - Offutt, Chris, 1958- (Offutt, Chris, 1958- Mick Hardin novels., 2023)
"Mick Hardin is home on leave, recovering from an IED attack, when a body is found in the center of town. It'sBarney Kissick, the local heroin dealer, and the city police see it as an occupational hazard. But when Barney's mother, Shifty, asks Mick to take a look, it seems there's more to the killing than it seems. Mick should be rehabbing his leg, signing his divorce papers, and getting out of town--and mos tof all, staying out of the way of his sister Linda's reelection as Sheriff--but he keeps on looking, and suddenly he's getting shot at himself. A dark, pacy crime novel about grief and revenge, and the surprises hidden below the surface, Shifty's Boys is a tour de force that confirms Chris Offutt's Mick Hardin as one of the most appealing new investigators in fiction" --